Issues of implementing the state program of energy saving and energy efficiency - Borshcheniuk, Vera; Semeryanova, Nina; Filatova, Uliana; Nikolaeva, Darya; Frolova, Elena (E3S web of conferences, 2019)
The article discusses the main issues of energy saving and energy efficiency in the Russian Federation, in particular, the issues of implementing state policy and development of energy management in the region. The authors define the concept of “energy saving” through the prism of subject of regulation, which more fully reveals the whole range of relations of energy saving, corresponding to the essence of legal regulation. The purpose of the study is to analyze legal and managerial problems of implementation of state program on energy saving and energy efficiency in the framework of regional management. The scientific novelty of the study consists in studying problems of energy saving and energy efficiency in the implementation of regional legislative establishments and issues of effectiveness of energy management in the region. The leading approach to the study of this problem is dialectic, analysis, synthesis, formal legal and comparative legal method. Conclusions: First, the state program of energy saving and energy efficiency at the regional level is not being implemented effectively enough. The main problem lies in weak coordination policy of interaction between the region and municipalities in organizing and conducting activities aimed at effective energy saving in the region. Secondly, the use of energy-saving technologies at industrial sites and business facilities is fairly low. Thirdly, there is no comprehensive legal study of this area of relations, and scientific papers are fragmentary.